2007
DOI: 10.1089/neu.2006.0167
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Spinal Cord Injury Are Not Estrogen-Dependent

Abstract: Recent attention has been given to gender differences in neurotrauma, and the anecdotal suggestion is that females have better outcomes than males, suggesting that circulating levels of estrogen (E(2)) may be neuroprotective. In order to address this issue, both young adult male and ovariectomized female rats were subjected to a T10 spinal cord injury (SCI), and E2 levels were maintained at chronic, constant circulating levels. Animals were clinically evaluated for locomotor changes using the Basso-Beattie-Bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 37 publications
1
42
1
1
Order By: Relevance
“…Moreover, continuous administration of estradiol at low physiological doses (Samantaray et al, 2011) stimulates a greater neuroprotective response than that seen in normal cycling rats. These findings suggest that maintaining constant levels of estradiol promotes a greater neuroprotective effect, as well as some locomotor recovery, and these results are in contrast to some published studies (Baker and Hagg, 2005; Swartz et al, 2007). However, differences in the doses of estradiol used, regimen of infusion, and mode of administration have expanded the array of results reported (Elkabes and Nicot, 2014).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, continuous administration of estradiol at low physiological doses (Samantaray et al, 2011) stimulates a greater neuroprotective response than that seen in normal cycling rats. These findings suggest that maintaining constant levels of estradiol promotes a greater neuroprotective effect, as well as some locomotor recovery, and these results are in contrast to some published studies (Baker and Hagg, 2005; Swartz et al, 2007). However, differences in the doses of estradiol used, regimen of infusion, and mode of administration have expanded the array of results reported (Elkabes and Nicot, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…Swartz et al 2007 showed that exposure to estradiol at low (28.2 pg/mL) or high (72 pg/mL) doses did not improve locomotor recovery in injured female rats. Baker & Haggs in 2005 concluded that the level of estradiol at different stages of the estrous cycle did not affect the functional outcome after SCI.…”
Section: Introductionmentioning
confidence: 93%
“…Thus, in addition to their neuroprotective effects, in some circumstances estrogens may be neurotoxic or ineffective as neuroprotector agents. For example, pre-treatment with estradiol exacerbates ischaemic oxidative damage [48] and has no effect on spinal cord injury [49]. Furthermore, a recent review [50] suggested that estradiol is effective in the prevention of disease, but not as a treatment for existing diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Swartz et al 14 reported that the outcome of motor function after SCI in female rats was better than that in males. They also reported that the difference of outcome was not dependent on estrogen.…”
Section: Animalsmentioning
confidence: 99%